Authority Of The Traffic Police In Conducting Motor Vehicle Inspections In The Jurisdiction Deli Serdang Police - Rikson Junardo; T. Riza Zarzani (Yayasan Multidimensi Kreatif, 2024)
Transportation is a vital element in supporting economic growth, strengthening national unity, and influencing various aspects of life. The traffic and road transportation system plays a strategic role in facilitating the movement of goods and services, emphasizing the need for its development to ensure security, welfare, and order. However, traffic violations, such as not wearing helmets, running red lights, or lacking proper documentation, have become prevalent and habitual among road users. Law Number 22 of 2009 regulates traffic and road transportation to address these issues, empowering law enforcement to take actions such as inspections, vehicle seizures, and imposing penalties. The Traffic Police play a crucial role in enforcing these regulations, guided by various legal frameworks, including Supreme Court Regulation No. 12 of 2016, which simplifies the judicial process for traffic violations. This study focuses on the Deli Serdang Police's authority in conducting motor vehicle inspections and the challenges they face. The research aims to analyze the implementation of this authority and identify obstacles encountered during enforcement. The findings underscore the need for enhanced legal awareness and community discipline through socialization efforts, aiming to foster a more law-abiding culture in traffic behavior.